RFID-Aided Tracking System to Improve Work Efficiency of Scaffold Supplier: Stock Management in Australasian Supply Chain - Moon, S.; Xu, S.; Hou, L.; Wu, Changzhi; Wang, X.; Tam, V. (American Society of Civil Engineers, 2018)
© 2017 American Society of Civil Engineers. The potential benefits of applied radio-frequency identification (RFID)-aided systems have been studied by many construction research projects. After reviewing previous works, this paper presents a self-developed system with the focus of a specific case in Australia. The system enables efficient material tracking, aiming for productivity improvement in the case. Initial site observations confirmed the need for an object-oriented material tracking system based on the principles of lean thinking and logistics qualities. Subsequently, a system was designed to activate a proposed method for optimizing material management during the supplier phase of the mega construction project. The experiments in this paper finally present two main streams: (1) performance testing of the system; and (2) productivity measure. As a result of performance testing, the tracking system was successful in locating the distributed 23 tags within an average range of 3.40 m. Supported by this system, the field productivity measurements consisting of four trailer-loading works (two lead and two tail trailers) quantified the feasible benefit of its application. The RFID-aided system facilitated the improvement of work performance, resulting in 10.14 (lead) and 11.80% (tail) productivity improvement. This research project therefore validated the benefits of RFID application in a construction supply chain by measuring its true value via the productivity improvements.